Wellbore blockage in shale gas wells: mechanical properties and a physical unblocking model - Zou, Longqing; Xiao, Jianfeng; Yang, Liang; Deng, Cai; Wang, Yixuan; Deng, Shaoping (Frontiers in Earth Science, 2025)
Wellbore blockage is a significant challenge hindering the efficient production of shale gas in the Sichuan-Chongqing region. To enable precise unblocking, it is crucial to understand the physical and mechanical properties of these complex downhole deposits. This study conducted a comprehensive analysis of blockage samples retrieved from a shale gas well in the Weiyuan area. We employed X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS), and thermogravimetric analysis (TG-DTG) to characterize the samples’ composition, microstructure, and thermal behavior. The results identified the blockage as a complex mixture primarily composed of quartz, Fe3O4, BaSO4, rock cuttings, and rubber particles. Furthermore, artificial blockage samples were fabricated under simulated downhole stress conditions (1–45 MPa) to evaluate their mechanical properties. Tests revealed that both compressive and shear strength increased with the forming stress. Based on the acquired mechanical parameters, a mechanical model was established to predict the pressure differential required to dislodge a blockage by wellhead pressurization. The model indicates that for blockages longer than half the pipe diameter (L > D/2), the required pressure becomes impractically high, rendering this method ineffective and necessitating combined unblocking strategies. This research provides a scientific basis for optimizing unblocking techniques and ensuring the safe, efficient development of shale gas resources.